Dopant‐Free Spiro‐Triphenylamine/Fluorene as Hole‐Transporting Material for Perovskite Solar Cells with Enhanced Efficiency and Stability. (29th January 2016) - Wang, Ya‐Kun; Yuan, Zhong‐Cheng; Shi, Guo‐Zheng; Li, Yong‐Xi; Li, Qian; Hui, Fei; Sun, Bao‐Quan; Jiang, Zuo‐Quan; Liao, Liang‐Sheng
Abstract : Chemical doping is often used to enhance electric conductivity of the conjugated molecule as hole‐transporting material (HTM) for the application in optoelectronics. However, chemical dopants can promote ion migration at the electrical field, which deteriorates the device efficiency as well as increases the fabrication cost. Here, two star HTMs, namely 2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxyphenyl‐amine) 9, 9′‐spirobifluorene (Spiro‐OMeTAD) and poly(triarylamine) are subjeted to chemical combination to yield dopant‐free N2, N2, N2′, N2′, N7, N7, N7′, N7′‐octakis(4‐methoxyphenyl)‐10‐phenyl‐10H‐spiro[acridine‐9, 9′‐fluorene]‐2, 2′, 7, 7′‐tetraamine (SAF‐OMe). The power conversion efficiencies (PCEs) of 12.39% achieved by solar cells based on pristine, dopant‐free SAF‐OMe are among the highest reported for perovskite solar cells and are even comparable to devices based on chemically doped Spiro‐OMeTAD (14.84%). Moreover, using a HTM comprised of SAF‐OMe with an additional dopant results in a record PCE of 16.73%. Compared to Spiro‐OMeTAD‐based devices, SAF‐OMe significantly improves stability. Abstract : A dopant‐free hole‐transporting material (HTM), N2, N2, N2′, N2′, N7, N7, N7′, N7′‐octakis(4‐methoxyphenyl)‐10‐phenyl‐10H‐spiro[acridine‐9, 9′‐fluorene]‐2, 2′, 7, 7′‐tetraamine (SAF‐OMe), is developed and implemented for use in perovskite solar cells. The power conversion efficiency (PCE) achieved by using SAF‐OMe as HTM is 12.39%, more than two times the reference 2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxyphenyl‐amine)9, 9′‐spirobifluorene (Spiro‐OMeTAD).